A PRELIMINARY REPORT ON THE MICRODISTRIBUTION OF BLACK FLY (DIPTERA: SIMULIIDAE) LARVAE IN RELATION TO HABITAT QUALITY THE SERRA DOS ÓRGÃOS REGION, BRAZIL - Pinto, Marlon José Ribeiro; Lucena, Luana Braz de; Maia, Amanda; Docile, Tatiana Nascimento; Figueiró, Ronaldo (Acta Scientiae et Technicae; v. 2 n. 2 (2014), 2014)
Black flies (Diptera: Simuliidae) are a worldwide distributed insect Family, comprised of more than 2,400 known species, most of which have hematophagous habits when adults, some of them being vectors of the Onchocerciasis and the Mansonelosis. Black fly larvae are filter feeding, and literature indicates that their distribution on a local scale is determined by microhabitat features, such as water current velocity, and habitat integrity degree. In this paper, preliminary data about the microdistribution of black flies is presented, and related to environmental traits such as water current velocity and habitat integrity.